Mendel: corroboration of the idea of binary trait coding by methods of statistical physics - О. V. Trapezov (Вавиловский журнал генетики и селекции)
The paper by the Augustinian friar Gregor Johann Mendel “Experiments on Plant Hybridization” laid the foundation of the new field of knowledge, genetics, 150 years ago. It claimed that any character was determined by two factors. On the one hand, the Mendelian idea of binary coding of a character was inspired by Christian Doppler, with whose department Mendel was contacting for seven years. On the other hand, the regularities discovered by Mendel confirmed the intuitive notion of the divine principle based on rational foundations. Pythagoras was the first to point to the spiritual grounds of being. The world had been created by the number, and the number is a nonmaterial and insensuous entity. All students of heredity before Mendel traced the fate of a character in a succession of generations. Instead, to unveil the heredity mechanism, Mendel traced the fates of two invisible factors that determined the character. Probably, the ideas of binary combinations and mathematical probabilistic variants arose from Mendel’s long meditation and an imaginary experiment. Experiments on pea crosses were undertaken just in order to test the idea of a set of invisible determinants. Methods borrowed from statistical physics allowed Mendel to decrypt the process occurring in experiments with the pea model: The fate of a character was determined by action of two invisible factors.